A method for flame drawing low-hydroxyl quartz fibers
Patent Information
- Application Number
- CN202611455980.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-18
- Publication Date
- 2026-10-27
AI Technical Summary
其中,电熔工艺由于无含水燃烧气氛,纤维羟基含量较低,但设备投资与运行能耗巨大,且难以直接稳定拉制数微米级的超细多丝束纤维;氢氧焰拉丝燃烧产物全部为水蒸气,通常需经粗棒高温长时间真空脱羟后进行电熔二次拉细,再配合高速拉丝工序,工艺流程繁琐且设备成本居高不下;而采用天然气/氧气开放火焰进行棒法多孔拉丝时,天然气燃烧产生大量的高温高分压水蒸气,在开放火焰熔融区极易与石英熔体接触并发生反应生成结构羟基,加之拉出的纤维在出火焰区后于开放环境中降温,容易与环境湿气发生反应引入额外羟基,导致常规火焰法制备的石英纤维羟基含量偏高,难以直接满足高品质低介电电子布的应用要求
[0015]本发明的有益效果在于:通过在拉丝前对小直径石英玻璃原料棒进行特定温和条件的真空预脱羟处理,在高效脱除原料内部羟基的同时,避免了高温长时间脱羟引发的细棒过热弯曲变形与表面析晶隐患;通过控制燃烧器进行微氧化燃烧,杜绝了还原性火焰引起的碳粒污染与缺氧色心缺陷,并与沿纤维丝束宽度向下倾斜喷射的狭缝式干燥气幕相协同,在维持稳定拉丝的同时将火焰燃烧生成的高温水蒸气平稳向外侧排开,阻断了高温熔融区水蒸气与石英熔体的直接接触;通过在密封冷却通道内引入干燥气体进行顺流吹扫降温,使离开通道的纤维丝束表面温度迅速降至石英玻璃网络冻结温度以下,在无外界湿气侵扰的微正压干燥环境下阻断了降温阶段次生羟基的生成;再配合在纤维降温后常温涂覆浸润剂并在干燥环境中自然干燥成膜,利用本体硅氧网络完全冻结硬化的物理状态,杜绝了浸润剂水分向纤维本体内部的渗透;
Smart Images

Figure CN122977685A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of inorganic fiber manufacturing and special glass deep processing technology, specifically to a flame drawing method for preparing low-hydroxyl quartz fibers. Background Technology
[0002] Quartz fiber possesses excellent high-temperature resistance, chemical corrosion resistance, and high-frequency dielectric properties, making it a core insulating reinforcement material for electronic cloths on printed circuit boards in the fields of high-frequency communication and electronic information. The application of quartz fiber in electronic cloths places stringent requirements on its dielectric properties. Residual structural hydroxyl groups in the fiber body can increase dielectric loss and degrade insulation performance. Therefore, controlling the content of structural hydroxyl groups in quartz fiber is crucial to ensuring its high-frequency electrical performance.
[0003] Currently, the main processes for preparing quartz fibers include electrofusion, oxyhydrogen flame, and natural gas / oxygen flame. Among these, electrofusion, due to the absence of a water-containing combustion atmosphere, results in lower hydroxyl content in the fibers, but it requires significant equipment investment and energy consumption, and it is difficult to directly and stably draw ultrafine multi-filament fibers down to the micrometer level. Oxyhydrogen flame drawing produces only water vapor as combustion products, typically requiring a second electrofusion drawing after high-temperature, long-duration vacuum dehydroxylation of a coarse rod, followed by a high-speed drawing process, making the process cumbersome and the equipment cost high. When using a natural gas / oxygen open flame for rod-based porous fiber drawing, the combustion of natural gas generates a large amount of high-temperature, high-pressure water vapor, which readily contacts and reacts with the quartz melt in the open flame melting zone to generate structural hydroxyl groups. Furthermore, the drawn fibers cool in the open environment after exiting the flame zone, easily reacting with ambient moisture to introduce additional hydroxyl groups, resulting in a high hydroxyl content in quartz fibers prepared by conventional flame methods, making it difficult to directly meet the application requirements of high-quality, low-dielectric electronic fabrics. Summary of the Invention
[0004] The purpose of this invention is to provide a flame drawing method for preparing low-hydroxyl quartz fibers, which can completely cut off the introduction path of hydroxyl groups and stably prepare low-hydroxyl quartz fibers with excellent low dielectric properties and high drawing quality under low-cost natural gas open flame drawing conditions.
[0005] To achieve the above objectives, the present invention provides a method for preparing low-hydroxyl quartz fibers by flame drawing, comprising the following steps: Step S10: Place the quartz glass raw material rod with a diameter of 2-4 mm in a vacuum heat treatment furnace and perform vacuum pre-dehydroxylation treatment for 0.2-1 h at a heat treatment temperature of 900-1050℃ and a vacuum degree of ≤10 Pa in the furnace. Store the dehydroxylated quartz glass raw material rod in a dry environment. Step S20: Natural gas and oxygen are introduced into the burner for micro-oxidation combustion to heat and melt the ends of the quartz glass raw material rods arranged in a row. Step S30: A slit-type gas curtain is set below the burner along the width direction of the fiber bundle formed by melting and drawing the quartz glass raw material rod, and dry gas is sprayed toward the fiber bundle in a downward inclined direction to dissipate the water vapor generated by the flame combustion to the outside. Step S40: Introduce the fiber bundle into the sealed cooling channel located below the slit-type air curtain, and introduce dry gas into the sealed cooling channel to blow and cool the fiber bundle in the same direction, so that the surface temperature of the fiber bundle when it leaves the sealed cooling channel drops to below 400°C. Step S50: Apply a sizing agent to the fiber bundle that has left the sealed cooling channel and has a surface temperature below 45°C, then wind it into a filament cake and place the filament cake in a dry environment to allow it to stand and form a film naturally.
[0006] Optionally, in step S10: The heat treatment temperature for vacuum pre-dehydroxylation treatment is 950-1000℃, the vacuum degree inside the furnace is ≤1Pa, and the holding time is 0.3-0.6h.
[0007] Optionally, in step S10: The dew point of the storage environment for the dehydroxylated quartz glass raw material rods is ≤-40℃; Before heating and melting, the dehydroxylated quartz glass raw material rod is purged with dry hot air with a dew point ≤ -40℃ and a temperature of 80-120℃ for 30-60 seconds to remove surface adsorbed water vapor.
[0008] Optionally, in step S20: Natural gas and oxygen are mixed in excess oxygen according to the stoichiometric ratio for complete combustion, with the excess oxygen coefficient controlled at 1.02-1.10; Both natural gas and oxygen are preheated to 150-250°C before entering the burner; The intake flow rate and supply pressure of natural gas and oxygen are controlled through closed loop, with the intake flow rate fluctuation range controlled within ±2% and the supply pressure fluctuation range controlled within ±5%.
[0009] Optionally, the excess oxygen coefficient is 1.04-1.08.
[0010] Optionally, in step S30: The slit-type air curtain sprays dry gas in a downward-sloping direction of 5-15°. The slit-type air curtain is symmetrically arranged on both sides of the fiber bundle along the width direction of the fiber bundle, and the vertical distance between the air curtain nozzle and the flame melting zone is 150-300mm.
[0011] Optionally, in step S30: The drying gas is dry nitrogen or dry compressed air, and the injection flow rate of the drying gas is 5-20 L / min for every 100 mm of the fiber bundle width.
[0012] Optionally, in step S40: The sealed cooling channel is a natural cooling structure without a water-cooling jacket, and the channel length is 0.5-1.5m; The dry gas introduced into the sealed cooling channel is dry nitrogen or dry compressed air with a dew point ≤ -40℃, which forms a downward-flowing micro-positive pressure in the channel; The surface temperature of the fiber bundle drops below 300°C when it leaves the sealed cooling channel.
[0013] Optionally, steps S20 to S40 are performed in a melt drawing environment, wherein the temperature of the melt drawing environment is controlled at 20-28°C and the relative humidity is controlled at ≤60%. Step S50 is performed in a winding film-forming environment, wherein the temperature of the winding film-forming environment is controlled at 25-35℃, the relative humidity is controlled at 50-70%, and a weak lateral wind parallel to the end face of the yarn cake is provided, with a wind speed of 0.3-0.5m / s.
[0014] Optionally, in step S50: The sizing agent is a starch-based sizing agent, and the fiber bundle is coated using a rubber-coated roller. After coating, the fiber bundles are wound into a filament cake and then left to dry naturally in the winding and film-forming environment for 12-24 hours without being heated or dried.
[0015] The beneficial effects of this invention are as follows: By performing vacuum pre-dehydroxylation treatment on small-diameter quartz glass raw material rods under specific mild conditions before drawing, the internal hydroxyl groups of the raw material are efficiently removed while avoiding the risk of overheating, bending deformation, and surface crystallization caused by long-term high-temperature dehydroxylation; by controlling the burner to perform micro-oxidation combustion, carbon particle contamination and oxygen-deficient color center defects caused by reducing flames are eliminated, and in conjunction with the slit-type drying gas curtain that is sprayed downward along the width of the fiber bundle, the high-temperature water vapor generated by the flame combustion is smoothly discharged to the outside while maintaining stable drawing, thus blocking the direct contact between the water vapor in the high-temperature melting zone and the quartz melt; by introducing dry gas into the sealed cooling channel for co-current purging and cooling, the surface temperature of the fiber bundle leaving the channel is rapidly reduced to below the freezing temperature of the quartz glass network, and the generation of secondary hydroxyl groups during the cooling stage is blocked in a micro-positive pressure drying environment without external moisture interference; furthermore, after the fiber is cooled, a sizing agent is applied at room temperature and then naturally dried in a drying environment to form a film, utilizing the physical state of complete freezing and hardening of the bulk silicon-oxygen network, preventing the penetration of sizing agent moisture into the fiber body; The various process steps of this invention work closely together, cutting off the introduction path of hydroxyl groups throughout the entire process, and stably preparing low-hydroxyl quartz fibers with both excellent low dielectric properties and high drawing quality under low-cost natural gas open flame drawing conditions.
[0016] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below with reference to the accompanying drawings. Attached Figure Description
[0017] Figure 1 This is a schematic flowchart illustrating a flame drawing method for preparing low-hydroxyl quartz fiber according to an embodiment of the present invention. Detailed Implementation
[0018] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0019] In the description of this invention, it should be noted that the terms "center," "upper," "lower," "left," "right," "vertical," "horizontal," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing the invention and for simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the invention. Furthermore, the terms "first," "second," and "third" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.
[0020] In the description of this invention, it should be noted that, unless otherwise explicitly specified and limited, the terms "installation," "connection," and "linking" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art can understand the specific meaning of the above terms in this invention based on the specific circumstances. Furthermore, the technical features involved in the different embodiments of this invention described below can be combined with each other as long as they do not conflict with each other.
[0021] Please see Figure 1 A preferred embodiment of this application illustrates a flame-drawing method for preparing low-hydroxyl quartz fibers, comprising the following steps: Step S10: Place the quartz glass raw material rod with a diameter of 2-4 mm in a vacuum heat treatment furnace and perform vacuum pre-dehydroxylation treatment for 0.2-1 h at a heat treatment temperature of 900-1050℃ and a vacuum degree of ≤10 Pa in the furnace. Store the dehydroxylated quartz glass raw material rod in a dry environment. Step S20: Natural gas and oxygen are introduced into the burner for micro-oxidation combustion to heat and melt the ends of a row of quartz glass raw material rods arranged side by side; Step S30: Set a slit-type gas curtain below the burner along the width direction of the fiber bundle formed by melting and drawing out the quartz glass raw material rod, and spray dry gas toward the fiber bundle in a downward inclined direction to dissipate the water vapor generated by the flame combustion to the outside. Step S40: Introduce the fiber bundle into the sealed cooling channel located below the slit-type air curtain, and introduce dry gas into the sealed cooling channel to blow and cool the fiber bundle in the same direction, so that the surface temperature of the fiber bundle when it leaves the sealed cooling channel drops to below 400°C. Step S50: Apply a sizing agent to the fiber bundle that has left the sealed cooling channel and has a surface temperature below 45°C, then wind it into a filament cake and place the filament cake in a dry environment to allow it to stand and form a film naturally.
[0022] According to the embodiments of the present invention, the structural hydroxyl groups in the quartz glass mainly originate from the bonded hydroxyl groups formed by the attack of water vapor on the silicon-oxygen bonds in the molten high-temperature zone and their reaction. This reaction is extremely vigorous above the strain point of the quartz glass (approximately 1070°C). This invention employs a gentle and efficient vacuum pre-dehydroxylation process on small-diameter fine quartz rods in step S10, eliminating hydroxyl groups within the raw material at the source and preventing high-temperature softening deformation and surface crystallization of the fine rods. Step S20, combined with micro-oxidation combustion and step S30, with a downward-tilting slit gas curtain for isolation, pushes away the large amount of high-temperature water vapor generated by open flame combustion, blocking hydroxyl erosion in the high-temperature melting zone. Step S40, through downstream blowing of dry gas in a sealed cooling channel, rapidly cools the fibers to below 400°C before entering the workshop environment. Since the silicon-oxygen network of the quartz glass is fully frozen below 400-500°C, external water molecules cannot diffuse into the bulk, thus completely eliminating secondary hydroxyl groups generated by the reaction of moisture in the cooling environment. In step S50, the fibers are coated with a sizing agent below 45°C and naturally form a film in a dry environment. Because the bulk network is completely hardened and frozen, moisture in the sizing agent will not penetrate into the bulk. The entire process achieves synergistic hydroxyl control throughout the entire process under low-cost natural gas / oxygen open flame conditions, resulting in fibers with excellent dielectric properties.
[0023] The following detailed description uses specific examples: In step S10, the heat treatment temperature for vacuum pre-dehydroxylation is further preferably 950-1000℃, the vacuum degree in the furnace is further preferably ≤1Pa, and the holding time is further preferably 0.3-0.6h. The silica purity of the quartz glass raw material rod is ≥99.99%. If the high-temperature, long-time dehydroxylation parameters for large-sized thick rods (e.g., 15-40mm thick rods) are directly applied to 2-4mm thin rods, the thin rods are very prone to softening, bending, and deformation under their own weight at high temperatures, and cristobalite crystals are easily generated on the surface, which disrupts the continuity and uniformity of subsequent wire drawing. The mild and rapid-effect parameters defined in this invention are set according to the physical characteristics of thin rods having a large specific surface area and fast thermal conductivity. The thinner the rod diameter, the shorter the holding time, which fully removes the hydroxyl groups inside the raw material while maintaining the straightness of the thin rod and the absence of surface crystallization.
[0024] The dew point of the dehydroxylated quartz glass raw material rods is strictly controlled to be ≤-40℃. Before heating, melting, and drawing, the dehydroxylated quartz glass raw material rods are purged with dry hot air (dew point ≤-40℃, temperature 80-120℃) for 30-60 seconds to remove surface-adsorbed moisture. This hot air purging can quickly remove trace amounts of physically adsorbed moisture from the surface during transportation or storage without damaging the rod's quality, thus eliminating the need for strict continuous storage and use time limits.
[0025] In step S20, natural gas and oxygen are mixed in excess oxygen according to the stoichiometric ratio for complete combustion, with the excess oxygen coefficient controlled at 1.02-1.10, preferably 1.04-1.08. Both natural gas and oxygen are preheated to 150-250℃ before entering the burner. The inlet flow rate and supply pressure of natural gas and oxygen are controlled through closed-loop control, with the inlet flow rate fluctuation range controlled within ±2% and the supply pressure fluctuation range controlled within ±5%. The main component of natural gas is methane. The natural gas / oxygen flame temperature is typically between 2000-2200℃, with the melting zone temperature exceeding 1700℃. The combustion reaction itself inevitably generates water vapor. Gas preheating does not change the molar amount of combustion products, but preheating the reaction gases to 150-250℃ effectively prevents condensation in the pipeline, greatly improving combustion stability, flame rigidity, and the uniformity of temperature distribution across the burner width. The slightly excess oxygen coefficient eliminates reducing flames and avoids fine carbon black particle contamination caused by high-temperature oxygen deficiency, as well as oxygen-deficient color core defects in quartz glass. Intake flow is controlled in a closed-loop manner using a mass flow controller to ensure a constant and stable air-fuel ratio.
[0026] In step S30, a slit-type air curtain sprays dry gas at a downward tilt of 5-15°. The slit-type air curtain is symmetrically arranged on both sides of the fiber bundle along its width. The vertical distance between the air curtain nozzles and the flame melting zone is 150-300 mm, preferably about 200 mm. The specific distance is fine-tuned on-site to ensure stable combustion of the flame above without disturbing it. The dry gas is preferably dry nitrogen or dry compressed air with a dew point ≤-40℃, more preferably ≤-50℃. The spray flow rate of the dry gas is 5-20 L / min per 100 mm of fiber bundle width. This invention employs a flat, symmetrically arranged, downward-tilted slit air curtain, specifically designed for a single-row fiber bundle drawn from dozens to hundreds of thin rods. Without interfering with flame combustion, it forms a localized shielding zone with low water vapor partial pressure on both sides of the fiber bundle, smoothly pushing the high-temperature, water-containing flue gas generated in the flame zone downwards and outwards, reducing the spread of high-temperature water vapor along the fiber bundle and its contact with the newly formed fibers.
[0027] In step S40, the sealed cooling channel is a natural cooling structure without a water-cooling jacket, with a channel length of 0.5-1.5m, preferably 0.8-1.2m, and the tube body is made of stainless steel or heat-resistant glass. The dry gas introduced into the sealed cooling channel is dry nitrogen or dry compressed air with a dew point ≤-40℃. The gas flows downwards and forms a slight positive pressure in the channel, preventing external moisture from flowing back into the channel. The surface temperature of the fiber bundle when it leaves the sealed cooling channel drops to below 400℃, preferably below 300℃. The strain point of quartz glass is approximately 1070℃. Below 400-500℃, its silicon-oxygen network is fully frozen, making it extremely difficult for water molecules to diffuse into the bulk. Therefore, controlling the outlet temperature below 400℃ cuts off the structural hydroxyl reaction channel. This invention does not aim to force-cool the fibers to below 200℃ or room temperature, and the outer wall of the channel is not equipped with a forced water-cooling jacket. Too low a surface temperature would lead to an increase in the wetting angle of the subsequent water-based wetting agent and a deterioration in the spreading performance.
[0028] The fiber drawing workshop is spatially divided into two independent temperature and humidity control zones: Steps S20 to S40 are carried out in a molten fiber drawing environment, which includes the area around the burner, slit-type air curtain, and sealed cooling channel, with the ambient temperature controlled at 20-28℃ and the relative humidity controlled at ≤60%; Step S50 is carried out in a winding and film forming environment, with the temperature controlled at 25-35℃ and the relative humidity controlled at 50-70%, and a weak lateral airflow parallel to the end face of the fiber cake, with a wind speed of 0.3-0.5m / s. The weak lateral airflow flows parallel to the end face of the fiber cake, without directly blowing onto the fine fiber bundles, which accelerates the uniform evaporation of moisture on the surface of the fiber cake and avoids disrupting the fiber bundles and causing flyaways and breakage.
[0029] In step S50, a starch-based sizing agent is used, and the fiber bundle is uniformly coated at room temperature using a rubber-coated roller. During coating, the surface temperature of the fiber bundle is below 45°C, and the quartz network is in a frozen-hardened state, preventing moisture in the sizing agent from penetrating into the matrix to generate structural hydroxyl groups. The coated fiber bundle is directly wound into a filament cake, without being heated in a drying oven, and is allowed to naturally dry for 12-24 hours in a winding film-forming environment at 25-35°C and 50-70% relative humidity. This process is seamlessly integrated with the subsequent electronic fabric weaving process, and the post-processing of the electronic fabric after weaving is uniformly switched to hot desizing at temperatures above 400°C followed by composite coupling agent treatment.
[0030] As an alternative implementation, if high-purity synthetic quartz glass raw material rods with extremely low hydroxyl background are directly purchased (e.g., using silicon tetrachloride chemical vapor phase synthesis material with a hydroxyl content of less than 1 ppm at the factory), the vacuum pre-dehydroxylation treatment process in step S10 can be omitted. Before the raw material rods are drawn into fibers, they can be directly fed into the combustion and fiber drawing process in step S20 after being purged with dry hot air at a dew point ≤ -40℃ and a temperature of 80-120℃ for 30-60 seconds. In addition, in addition to using an independent pipeline electric preheater, the preheating method for natural gas and oxygen can also be to directly set a heat exchange chamber in the burner shell and use the residual heat of the flame to preheat the intake pipe.
[0031] In one specific embodiment, the raw material is a high-purity quartz glass rod with a silica purity of ≥99.99% and a diameter of 2.0 mm.
[0032] Step S10: Place the thin rod in a vacuum heat treatment furnace and keep it at a heat treatment temperature of 980℃ and a vacuum degree of ≤3Pa for 0.4h. After taking it out of the furnace, seal it and store it in a drying cabinet with a dew point of ≤-40℃. Before putting it on the machine, blow the thin rod with dry hot air at a temperature of 100℃ and a dew point of ≤-40℃ for 45s.
[0033] Step S20: Natural gas and oxygen are controlled in a closed loop by a mass flow controller. The excess oxygen coefficient is set to 1.05. The intake gas is preheated to 200°C. The intake gas flow fluctuation is controlled within ±2%, and the gas supply pressure fluctuation is controlled within ±5%. The burner melts the ends of a row of dozens of parallel thin rods.
[0034] Step S30: A slit-type gas curtain is symmetrically set on both sides along the width of the fiber bundle at a position 200mm below the burner. The nozzle is tilted downward at 10° to spray dry nitrogen with a dew point ≤ -50℃. The spray flow rate is controlled at 10L / min (corresponding to 100mm fiber bundle width).
[0035] Step S40: A 1.0m long stainless steel sealed cooling channel is connected below the air curtain. Dry nitrogen gas with a dew point ≤ -40℃ is introduced to purge under a slight positive pressure in the same direction. The surface temperature of the fiber bundle when it leaves the channel drops to about 50℃.
[0036] Step S50: The environment in the melting and drawing zone is controlled at 25°C and 55% relative humidity; the environment in the winding and film forming zone is controlled at 30°C and 60% relative humidity, supplemented by a weak transverse wind of 0.4 m / s parallel to the end face of the fiber cake; the fiber bundle is coated with starch-type sizing agent by a rubber roller at a surface temperature below 45°C, wound into a fiber cake, and then left to stand in the film forming zone for 18 hours to dry naturally into a film.
[0037] The obtained quartz fiber monofilament has a diameter of 6.0±0.3μm, and the drawing process is continuous and stable without fiber breakage. The test results show that the hydroxyl content of the fiber body is ≤30ppm, and the dielectric constant is less than 3.65 and the dielectric loss is less than 0.0035 at a test frequency of 10GHz. This is significantly better than the traditional natural gas flame method products that do not use this process (the hydroxyl content of traditional flame method products is usually 150-250ppm and the dielectric constant is greater than 3.80), and fully meets the application index requirements of high-end high-frequency electronic cloth.
[0038] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0039] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A method for preparing low-hydroxyl quartz fiber by flame drawing, characterized in that, Includes the following steps: step S10: Place quartz glass raw material rods with a diameter of 2-4mm in a vacuum heat treatment furnace and perform vacuum pre-dehydroxylation treatment for 0.2-1h under the conditions of heat treatment temperature of 900-1050℃ and vacuum degree ≤10Pa in the furnace. Store the dehydroxylated quartz glass raw material rods in a dry environment. Step S20: Natural gas and oxygen are introduced into the burner for micro-oxidation combustion to heat and melt the ends of the quartz glass raw material rods arranged in a row. Step S30: A slit-type gas curtain is set below the burner along the width direction of the fiber bundle formed by melting and drawing the quartz glass raw material rod, and dry gas is sprayed toward the fiber bundle in a downward inclined direction to dissipate the water vapor generated by the flame combustion to the outside. Step S40: Introduce the fiber bundle into the sealed cooling channel located below the slit-type air curtain, and introduce dry gas into the sealed cooling channel to blow and cool the fiber bundle in the same direction, so that the surface temperature of the fiber bundle when it leaves the sealed cooling channel drops to below 400°C. Step S50: Apply a sizing agent to the fiber bundle that has left the sealed cooling channel and has a surface temperature below 45°C, then wind it into a filament cake and place the filament cake in a dry environment to allow it to stand and form a film naturally.
2. The method for preparing low-hydroxyl quartz fiber by flame drawing according to claim 1, characterized in that, In step S10: The heat treatment temperature for vacuum pre-dehydroxylation treatment is 950-1000℃, the vacuum degree inside the furnace is ≤1Pa, and the holding time is 0.3-0.6h.
3. The method for preparing low-hydroxyl quartz fiber by flame drawing according to claim 1 or 2, characterized in that, In step S10: The dew point of the storage environment for the dehydroxylated quartz glass raw material rods is ≤-40℃; Before heating and melting, the dehydroxylated quartz glass raw material rod is purged with dry hot air with a dew point ≤ -40℃ and a temperature of 80-120℃ for 30-60 seconds to remove surface adsorbed water vapor.
4. The method for preparing low-hydroxyl quartz fiber by flame drawing according to claim 1, characterized in that, In step S20: Natural gas and oxygen are mixed in excess oxygen according to the stoichiometric ratio for complete combustion, with the excess oxygen coefficient controlled at 1.02-1.10; Both natural gas and oxygen are preheated to 150-250°C before entering the burner; The intake flow rate and supply pressure of natural gas and oxygen are controlled through closed loop, with the intake flow rate fluctuation range controlled within ±2% and the supply pressure fluctuation range controlled within ±5%.
5. The method for preparing low-hydroxyl quartz fiber by flame drawing according to claim 4, characterized in that, The excess oxygen coefficient is 1.04-1.
08.
6. The method for preparing low-hydroxyl quartz fiber by flame drawing according to claim 1, characterized in that, In step S30: The slit-type air curtain sprays dry gas in a downward-sloping direction of 5-15°. The slit-type air curtain is symmetrically arranged on both sides of the fiber bundle along the width direction of the fiber bundle, and the vertical distance between the air curtain nozzle and the flame melting zone is 150-300mm.
7. The method for preparing low-hydroxyl quartz fiber by flame drawing according to claim 1 or 6, characterized in that, In step S30: The drying gas is dry nitrogen or dry compressed air, and the injection flow rate of the drying gas is 5-20 L / min for every 100 mm of the fiber bundle width.
8. The method for preparing low-hydroxyl quartz fiber by flame drawing according to claim 1, characterized in that, In step S40: The sealed cooling channel is a natural cooling structure without a water-cooling jacket, and the channel length is 0.5-1.5m; The dry gas introduced into the sealed cooling channel is dry nitrogen or dry compressed air with a dew point ≤ -40℃, which forms a downward-flowing micro-positive pressure in the channel; The surface temperature of the fiber bundle drops below 300°C when it leaves the sealed cooling channel.
9. The method for preparing low-hydroxyl quartz fiber by flame drawing according to claim 1, characterized in that, Steps S20 to S40 are carried out in a melt drawing environment, wherein the temperature of the melt drawing environment is controlled at 20-28℃ and the relative humidity is controlled at ≤60%. Step S50 is performed in a winding film-forming environment, wherein the temperature of the winding film-forming environment is controlled at 25-35℃, the relative humidity is controlled at 50-70%, and a weak lateral wind parallel to the end face of the yarn cake is provided, with a wind speed of 0.3-0.5m / s.
10. The method for preparing low-hydroxyl quartz fiber by flame drawing according to claim 1 or 9, characterized in that, In step S50: The sizing agent is a starch-based sizing agent, and the fiber bundle is coated using a rubber-coated roller. After coating, the fiber bundles are wound into a filament cake and then left to dry naturally in the winding and film-forming environment for 12-24 hours without being heated or dried.